Wound Healing Activity Of Topical Application Of Aloe Vera Gel In Experimental Animal Models - K.C.HARITHA YADAV; J. RAVI KUMAR; S.ILIAS BASHA; G.R.DESHMUKH; RAVI GUJJULA; B.SANTHAMMA (International Journal of Pharma and Bio Sciences, 2012)
Aloe vera gel of 50% and 96.4% were tested for its wound healing activity by topical application in experimental rats. The effect of Aloe vera gel on wound healing was evaluated by wound excision model and histopathology was used to study the effect on wound healing. The effect produced by Aloe vera gel with reference to wound contraction, wound closure, decrease in surface area of wound, tissue regeneration at the wound site and histopathological characteristics were significant in treated rats. The effect of Aloe vera gel on biochemical studies revealed significant increase in collagen and decreased hexosamine content and malondialdehyde levels when compared with control. The present study thus provided scientific rationale for the traditional use of Aloe vera gel for management of wounds.